Simple and Fast Picomolar Detection of Ochratoxin A Using a Reusable Label Free Aptasensor Built with a Layer‐by‐layer Procedure. Issue 10 (11th July 2017) - Simão, Estéfani P.; Cao‐Milán, Roberto; Costa‐Pedro, Graciela; De Melo, Celso P.; Cao, Roberto; Oliveira, Maria D. L.; Andrade, Cesar A. S.
Abstract: A label free impedimetric aptasensor for simple, fast and reusable picomolar detections of Ochratoxin A (OTA) in grape juices was designed. Two main factors were observed to affect the accurate detections of the toxin: i‐lateral interactions between self‐assembled aptamers ii‐ adsorption of large molecules present in complex matrixes like grape juices. Lateral interactions between aptamers were minimized by constructing the aptasensor in a Layer‐by‐Layer procedure. The interferences associated to the unspecific and irreversible adsorption of large molecules present in grape juice, were reduced by submitting samples to ultrafiltration prior to analysis. With this protocol, a 0.12 pM limit of detection and 0.24 pM limit of quantification in spiked grape juices were achieved after only 5–7 mins of interaction with the samples. The presented aptasensor can be recovered after a simple immersion in hot water (90 °C) for ten minutes. Abstract :